Nouveaux biohorizons et propositions pour le découpage biozonal ammonitique du Barrémien supérieur du Sud-Est de la France [New biohorizons and proposal for a revision of the ammonite biozonation of the Upper Barremian of southeastern France] - Bert Didier; Bersac Stéphane; Delanoy Gérard (Carnets de Géologie, 2008)
A new ammonite biozonal scheme is proposed for the Upper Barremian of southeastern France. It takes into account faunal changes, sequence stratigraphy and historical data. Four new biohorizons are proposed. At present, three (formerly six) are accepted for the Upper Barremian: the Vandenheckei, Sartousiana and Giraudi biozones. The first contains three subzones, the Uhligi (current status discussed), the Sayni and the Barremense subzones, and two new biohorizons, the Marchandi and Breistrofferi biohorizons (top of the Barremense Subzone). The Sartousiana Biozone now includes the Limentinus, Provincialis and Feraudianus subzones. This last one lost its status of biozone because of paleontologic and stratigraphic arguments. Six biohorizons are recognized in the Sartousiana Biozone: the Limentinus, Provincialis, Casanovai, Feraudianus, Magnini and Autrani biohorizons. The Giraudi Biozone includes the Giraudi, Sarasini and Waagenoides subzones and the Giraudi, Emerici and Puzosianum biohorizons.